Transmenopausal Changes in Trabecular Bone Quality. (March 2014) - Gamsjaeger, Sonja; Brozek, Wolfgang; Recker, Robert; Klaushofer, Klaus; Paschalis, Eleftherios P
ABSTRACT Bone strength depends on its amount and quality. Bone quality includes its structural and material properties. Bone material properties are dependent on bone turnover rates. Remodeling rates are significantly increased immediately after menopause. In the present study, we used Raman microspectroscopic analysis of double iliac crest biopsies with a spatial resolution of 1 µm obtained before and immediately after menopause (1 year after cessation of menses) in healthy females to investigate changes in material properties attributable to menopause. In particular, the mineral/matrix ratio, the relative proteoglycan and lipid content, the mineral maturity/crystallinity, and the relative pyridinoline collagen cross‐link content were determined in trabecular bone as a function of surface metabolic activity and tissue age. The results indicate that significant changes (specifically in mineral/matrix ratio) were evident at active bone forming surfaces, whereas the relative proteoglycan content was altered at resorbing surfaces. These changes were not accompanied by altered mineral content or quality as monitored by Raman microspectroscopic analysis. © 2014 American Society for Bone and Mineral Research.